Shed female caribou antlers extend records of calving activity on the Arctic National Wildlife Refuge by millennia - Miller, Joshua H.; Wald, Eric J.; Druckenmiller, Patrick (Frontiers in Ecology and Evolution, 2023)
Caribou (Rangifer tarandus) have among the longest annual migrations of any terrestrial mammal as they move from winter ranges to spring calving grounds. Biomonitoring records indicate broad consistencies in calving geography across the last several decades, but how long have herds used particular calving grounds? Furthermore, how representative are modern patterns of calving geography to periods that pre-date recent climatic perturbations and increased anthropogenic stresses? While modern ecological datasets are not long enough to address these questions, bones from past generations of caribou lying on the tundra provide unique opportunities to study historical calving geography. This is possible because female caribou shed their antlers within days of giving birth, releasing a skeletal indicator of calving. Today, the Coastal Plain of the Arctic National Wildlife Refuge (Alaska) is a key calving ground for the Porcupine Caribou Herd (PCH). To test the duration across which caribou have used this area as a calving ground, we radiocarbon dated three highly weathered female antlers collected from tundra surfaces on the Coastal Plain. Calibrated radiocarbon dates indicate that these antlers were shed between ~1,600 and more than 3,000 calendar years ago. The antiquity of these shed antlers provides the first physical evidence of calving activity on the PCH calving grounds from previous millennia, substantiating the long ecological legacy of the Coastal Plain as a caribou calving ground. Comparisons to published lake core records also reveal that dates of two of the antlers correspond to periods with average summer temperatures that were warmer than has been typical during the last several decades of biomonitoring. This finding expands the range of climatic settings in which caribou are known to use the current PCH calving grounds and suggests that the Coastal Plain of the Arctic Refuge may remain an important caribou calving ground during at least portions of predicted future warming. Discarded skeletal materials provide opportunities to assess the historical states of living populations, including aspects of reproductive biology and migration. Particularly in high-latitude settings, these insights can extend across millennia and offer rare glimpses into the past that can inform current and future management policies.